2003
DOI: 10.1111/j.1523-1739.2003.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Historic Livestock Grazing on Vegetation at Chaco Culture National Historic Park, New Mexico

Abstract: Livestock grazing is the most ubiquitous land use in western North America, yet it rarely has been studied in a controlled manner because of the lack of large areas free of grazing. We compared the ecological effects of three grazing treatments-long-term protection, short-term protection, and currently grazed-at Chaco Culture National Historic Park in northern New Mexico. Chaco has a long history of human habitation and is now one of the largest grazing exclosures in the American West. We studied the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
1
21
1
7
Order By: Relevance
“…These results show that the abandonment of grazing on rocky pastures encourages progressive succession and development of macchia characterized by reduced plant diversity. FUHLENDORF et al (2001) andFLOYD et al (2003) also confi rm that very intensive grazing reduces the number of species and lays bare the soil surface. By examining the response of semi-natural Mediterranean pastures to the grazing intensity NOY-MEIR et al (1989) found changes in most of the studied taxa observed within 15 fenced plots.…”
Section: Sheep Grazing Intensity and Plant Diversitymentioning
confidence: 89%
“…These results show that the abandonment of grazing on rocky pastures encourages progressive succession and development of macchia characterized by reduced plant diversity. FUHLENDORF et al (2001) andFLOYD et al (2003) also confi rm that very intensive grazing reduces the number of species and lays bare the soil surface. By examining the response of semi-natural Mediterranean pastures to the grazing intensity NOY-MEIR et al (1989) found changes in most of the studied taxa observed within 15 fenced plots.…”
Section: Sheep Grazing Intensity and Plant Diversitymentioning
confidence: 89%
“…These results are in agreement with what is known for smaller life-forms, as grasses and herbs experiencing faster succession after disturbance. For example, in mountain grasslands of Argentina (Nai-Bregaglio et al, 2002) and in the tropical dry forest of DRY FOREST'S CACTI COMMUNITY Sierra de Huautla, Mexico (De la O-Toris et al, 2012), a higher diversity and richness of herbs and grasses was found in disturbed areas compared to conserved ones (but see Floyd et al, 2003). In this study, seven out of nine cactus species and more than 55% of individuals registered in both forest types were ≤ 3 m in height.…”
Section: Discussionmentioning
confidence: 99%
“…We may expect a differential effect of disturbance in the structure of a community depending from dominant life-form. For example, diversity, richness, and evenness of herbs and grasses increase under extensive cattle ranching in pasturelands (Nai-Bregaglio et al, 2002;Floyd et al, 2003;Hayes and Holl, 2003), whereas livestock presence affects negatively tree richness and diversity in the dry forests (Roth, 1999;González-Iturbe et al, 2002;Stern et al, 2002;VanderWerf, 2004). On the other hand, selective logging may not affect tree evenness in the dry forest (Monroy-Ortiz, 1997), but livestock presence does (Sánchez-Velásquez et al, 2002).…”
mentioning
confidence: 99%
“…El pastoreo siempre reduce y hasta puede llegar a eliminar la masa vegetal (Floyd et al, 2003), existiendo una pérdida proporcional de biomasa con el grado de presión del ganado (Hayes y Holl, 2003). Sin embargo, en varios estudios en pastizales naturales se ha registrado un aumento en la riqueza de hierbas debido al pastoreo (p.…”
Section: Jessica De La O-toris Et Alunclassified
“…En una selva estacional de Costa Rica, la presencia del ganado causó un cambio en la composición de la comunidad arbórea después de 30 años de pastoreo (Stern et al, 2002). Para cualquier ecosistema y forma de vida, la ganadería extensiva siempre tiene efectos negativos en la biomasa vegetal aunque en pastizales naturales, puede tener efectos positivos e inmediatos en la riqueza de hierbas y pastos (Floyd et al, 2003;McIntyre et al, 2003). Además, la ganadería, al afectar negativamente la densidad de árboles, podría tener un efecto indirecto positivo en el estrato herbáceo, debido al aumento de luz.…”
Section: Jessica De La O-toris Et Alunclassified